41 Use of sirolimus-coated balloon in de novo small vessel coronary lesions; mid-term follow-up from a two-centre registry. (17th July 2020) - Liu, Boyang; Khattak, Sophia; Ishaq, Mohammed; Athukorala, Sampath; Watkin, Richard; Lee, Kaeng; Pulikal, George; Ment, Jerome; Bhatia, Gurbir; Freestone, Bethan; Pitt, Michael; Basavarajaiah, Sandeep
Abstract : Aims: Drug coated balloons (DCB) in Europe is mainly used in restenotic lesions and this is endorsed by the European Society of Cardiology which gives class IA recommendations. However, some of the recent data suggest, it can also be considered in subset of denovo lesions especially small vessels (<3.0 cm). Most DCBs used elute Paclitaxcel, but there is no data on Limus eluting DCB, which is the drug of choice in currently available drug eluting stents. In this study, we report outcomes from the use of Limus eluting DCB (MagicTouch, Concept Medical, India) in de novo small vessel coronary lesions. Methods and Results: We included all patients treated with MagicTouch DCB between March 2018 and June 2019. The results are reported as cardiac death, target vessel myocardial infarction, target lesion revascularisation (TLR) and MACE (combination of cardiac death, target vessel MI and TLR). During the study period, 219-patients (with 243-lesions) with de novo lesions were treated with MagicTouch DCB. The mean age of patients were 66 +/- 10.7 years, 209 (77%) were male, 34% (n=75) had diabetes, 16% (n=34) had chronic kidney disease and 54% were in the setting of acute coronary syndrome (n=118). Predilatation was performed in 92% (222-lesions). Bailout stenting (with DES) was required in 13% lesions (n=32) and of which 18 were due to dissections and 14 were due to recoil >30% following DCB use. The mean diameter and length of DCBs were 2.29 mm and 24 mm respectively. During a median follow-up of 313-days (10-months) cardiac death was reported in 3 patients (1.4%). Target vessel MI was in 1.4% (n=2), TLR per lesion was 6.5% (n=16) and the MACE rate was 5.5% (n=12). There were no documented cases of acute vessel closure. Conclusion: The mid-term outcome from the first ever study on sirolimus eluting balloon in de novo small vessel lesions appears promising with low rates of hard endpoints, repeat rates of revascularisation and MACE rates despite complex group of patients (50% ACS, 34% diabetics and 14% CKD) and lesion subsets (small vessel and diffuse disease). We need longer follow-up which is ongoing and we will be able to report the outcomes from even longer follow-up during the BCS. Conflict of Interest: None